Rock slope stability assessment of limestone quarry; an example from Istanbul Cebeci region, Turkey - Yılmaz, Murat; Tuğrul, Atiye; Er, Selman; Ertin, Altay; Tokgöz, Nuray; AREL, ERSİN (Springer International Publishing Ag, Gewerbestrasse 11, Cham, Ch-6330, Switzerland, 2015)
The Cebeci Region is characterised by famous outcrops of Carboniferous Limestone which is mined out for aggregate production. The aim of this study is to investigate slope stability problems for heavily jointed karstic limestones in an aggregate quarry. Limestone quarries have turned into steep cliffs of bare rocks which threaten the safety of construction and have also negative influence on the aesthetics in the Cebeci Region. For this study, firstly, field studies were carried out involving detailed discontinuity surveys. Then, laboratory tests were conducted to determine physical, mechanical and elastic properties of the intact rock and shear strength parameters of the discontinuities for each different lithology. Kinematical analyses were performed to determine the potential kinematic failures and stability sites of the quarry. Also, finite element method analyses was carried out for the global stability of cut slopes with applying a number of different disturbance zones, parallel to the slope faces. According to the results of kinematic and numerical analysis, different types of failures are expected in different sites of quarry. Based on the field studies and stability analyses of the cut slopes, slope geometry optimization and necessary support measures such as wire mesh and rockfall barriers are suggested.
Keywords: Limestone; Slope stability; Kinematic analysis; Numerical analysis